2005
DOI: 10.1158/1078-0432.ccr-05-0035
|View full text |Cite
|
Sign up to set email alerts
|

Boron Neutron Capture Therapy of Cancer: Current Status and Future Prospects

Abstract: Background: Boron neutron capture therapy (BNCT) is based on the nuclear reaction that occurs when boron-10 is irradiated with low-energy thermal neutrons to yield high linear energy transfer A particles and recoiling lithium-7 nuclei. Clinical interest in BNCT has focused primarily on the treatment of high-grade gliomas and either cutaneous primaries or cerebral metastases of melanoma, most recently, head and neck and liver cancer. Neutron sources for BNCT currently are limited to nuclear reactors and these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
690
0
20

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 912 publications
(714 citation statements)
references
References 182 publications
4
690
0
20
Order By: Relevance
“…We have, therefore, initiated a prospective clinical trial where cetuximab, a monoclonal antibody directed at the epidermal growth factor receptor, is given immediately after BNCT (ClinicalTrials.gov identifier NCT00927147). Other potential approaches that might improve the efficacy of BNCT include sequential administration of BNCT with intensity-modulated radiotherapy, concomitant administration of platinum compounds, intra-arterial or prolonged infusion of the boron carrier (27), and novel boron carrier compounds (9). BNCT warrants further study also among a patient population with unresectable head-and-neck cancer as first-line treatment, perhaps as administered before conventional chemoradiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have, therefore, initiated a prospective clinical trial where cetuximab, a monoclonal antibody directed at the epidermal growth factor receptor, is given immediately after BNCT (ClinicalTrials.gov identifier NCT00927147). Other potential approaches that might improve the efficacy of BNCT include sequential administration of BNCT with intensity-modulated radiotherapy, concomitant administration of platinum compounds, intra-arterial or prolonged infusion of the boron carrier (27), and novel boron carrier compounds (9). BNCT warrants further study also among a patient population with unresectable head-and-neck cancer as first-line treatment, perhaps as administered before conventional chemoradiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…BNCT is based on the neutron capture reaction that occurs when nonradioactive boron ( 10 B) is irradiated with neutrons of low (thermal) energy. This causes a nuclear decay yielding high-energy a particles and recoiling lithium ( 7 Li) nuclei (9). Because a and 7 Li have short range in tissue and they produce dense ionization along their tracks, most radiation effect is local and occurs within the cells that contain boron.…”
Section: Introductionmentioning
confidence: 99%
“…The resonance-stabilized delocalization of the positive charge of DLCs, coupled with their inherent lipophilicity, leads to a decrease in the cost associated with the free energy change that accompanies the diffusion of DLCs through cell membranes, and provides the 5 driving force for their observed highly selective accumulation (>100 fold) in the mitochondrial matrix of cancer cells [13,17,18] and the associated high (>5 fold) difference between their cytoplasmic and extracellular concentrations [11]. Towards the development of highly selective target-specific anticancer agents that are applicable to boron neutron capture therapy (BNCT) of cancer, this study builds on preliminary evaluations that indicated the selective accumulation of boronated DLC compounds in cancer cells [19,20]. In particular, the experimental work focuses on the pharmacological evaluation at cellular and molecular level of four of these boron molecules, the molecular design of which combines the tumor-cell specificity of Moreover, molecular gene expression profiling has indicated that the DLC-carboranes exert their pharmacological properties through the activation of the p53/p21 axis, a crucial molecular pathway long known to control cell cycling and growth arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Dipyrromethanes 4 were prepared from the reaction of the corresponding benzaldehyde with an excess of pyrrole using TFA as the catalyst, in 70-86% yields, as previously reported. 25-27 The condensation of compounds 3 and 4a via a [2+2] methodology, 27-29 using BF 3 •OEt 2 for 1 h at room temperature, followed by oxidation with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) gave porphyrins 6a, 7a and H 2 OCP in 2.1, 6.3 and 8.5% yields, respectively, as major products. On the other hand, the condensation of 3 and 4b under similar conditions but using BF 3 •OEt 2 for only 4 min, afforded porphyrins 6b, 7b, 8b and H 2 OCP in 2.6, 8.0, 4.5 and 2.1% yields, respectively.…”
Section: Porphyrin Synthesesmentioning
confidence: 99%
“…25-27 The condensation of compounds 3 and 4a via a [2+2] methodology, 27-29 using BF 3 •OEt 2 for 1 h at room temperature, followed by oxidation with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) gave porphyrins 6a, 7a and H 2 OCP in 2.1, 6.3 and 8.5% yields, respectively, as major products. On the other hand, the condensation of 3 and 4b under similar conditions but using BF 3 •OEt 2 for only 4 min, afforded porphyrins 6b, 7b, 8b and H 2 OCP in 2.6, 8.0, 4.5 and 2.1% yields, respectively. Other porphyrins were also obtained as minor products (< 1% yield) as a result of the scrambling but were not isolated in sufficient amounts for characterization.…”
Section: Porphyrin Synthesesmentioning
confidence: 99%